Cover Feature: Characterisation of the Dynamic Interactions between Complex N‐Glycans and Human CD22 (ChemBioChem 1‐2/2020). (30th December 2019) - Di Carluccio, Cristina; Crisman, Enrique; Manabe, Yoshiyuki; Forgione, Rosa Ester; Lacetera, Alessandra; Amato, Jussara; Pagano, Bruno; Randazzo, Antonio; Zampella, Angela; Lanzetta, Rosa; Fukase, Koichi; Molinaro, Antonio; et al.
Abstract : Recognition and binding of host sialoglycans by human CD22 . On resting B‐cells, the cis interaction of h‐CD22 with sialoglycans exposed on the same plasma membrane results in the formation of CD22 homo‐oligomers. Conversely, trans interactions allow the recruitment of CD22 to the B‐cell receptor complex, thereby inhibiting its signaling. In their full paper, S. Martín‐Santamaría, R. Marchetti, A. Silipo, et al. on page 129 in Issue 1, 2020 (DOI: 10.1002/cbic.201900295 ) deepen the molecular insights into the binding mode and the conformation behavior of complex‐type N ‐glycans bound to h‐CD22. These new findings will enable the design of novel therapeutics with the aim of tackling autoimmune disorders and B‐cell malignancies.